Magnetic field depression within electron holes. Issue 7 (14th April 2015) - Vasko, I. Y.; Agapitov, O. V.; Mozer, F.; Artemyev, A. V.; Jovanovic, D.
Abstract We analyze electron holes that are spikes of the electrostatic field (up to 500 mV/m) observed by Van Allen Probes in the outer radiation belt. The unexpected feature is the magnetic field depression of about several tens of picotesla within many of the spikes. The earlier observations showed amplification or negligible perturbations of the magnetic field within the electron holes. We suggest that the observed magnetic field depression is due to the diamagnetic current of hot and highly anisotropic population of electrons trapped within the electron holes. The required trapped population should have a density up to 65% of the background plasma density, a temperature up to several keV, and a temperature anisotropy T⊥/T∥∼2. We argue that the observed electron holes could be generated due to injections of highly anisotropic plasma sheet electrons into the outer radiation belt. These electron holes may present a source of the seed population due to transport of trapped electrons to higher latitudes and can be potentially used for distant probing of plasma properties in their source region.